2021
DOI: 10.30892/gtg.34123-634
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder and Visitor Reflections of Sport Brand Positioning in South Africa

Abstract: The purpose of this paper was to identify stakeholder and visitor perceptions of brand images of the South African destination brand in order to examine how sport is utilised as a catalytic agent for achieving brand positioning. Following a mixed method approach, in-depth semistructured interviews were conducted with 24 sport, tourism, and government stakeholders. Survey questionnaires were administered with 403 sport event visitors at major events across South Africa. The results show congruence between stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…In line with the contemporary literature, the findings affirm that South Africa's destination marketing efforts directly and positively influence the travel motives of tourists (Avraham and Ketter, 2017;Khan, 2021;Lee, 2021a;Tessler et al, 2020), more-so nature and cultural experience-oriented international tourists (Gaffar et al, 2022). Furthermore, the findings corroborate the literature on the influence of destination marketing on how the citizens of tourism destinations are perceived (Hemmonsbey and Tichaawa, 2021;Tessler et al, 2020;Winter, 2009), as well as the extent to which governance (Wiysonge et al, 2022) immigration policy (Matiza and Slabbert, 2020) and negative events (Khan, 2021;Rasoolimanesh et al, 2021a;Wike et al, 2020) impact on the decision-making process of tourists via information symmetry (Batista-S anchez et al, 2022). Thus, the findings generally align with the notion of a symbiotic relationship between increased cognition and affective association (Gaffar et al, 2022;Nandonde, 2015).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with the contemporary literature, the findings affirm that South Africa's destination marketing efforts directly and positively influence the travel motives of tourists (Avraham and Ketter, 2017;Khan, 2021;Lee, 2021a;Tessler et al, 2020), more-so nature and cultural experience-oriented international tourists (Gaffar et al, 2022). Furthermore, the findings corroborate the literature on the influence of destination marketing on how the citizens of tourism destinations are perceived (Hemmonsbey and Tichaawa, 2021;Tessler et al, 2020;Winter, 2009), as well as the extent to which governance (Wiysonge et al, 2022) immigration policy (Matiza and Slabbert, 2020) and negative events (Khan, 2021;Rasoolimanesh et al, 2021a;Wike et al, 2020) impact on the decision-making process of tourists via information symmetry (Batista-S anchez et al, 2022). Thus, the findings generally align with the notion of a symbiotic relationship between increased cognition and affective association (Gaffar et al, 2022;Nandonde, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Malaysian law enforcement as a governance indicator was viewed as a critical antecedent to tourism demand (Seow et al , 2017). Aspects regarding the residents of the destination are perceived (people dimension) to be tolerance of cultural diversity and the friendliness of citizens, which have also been found to influence tourist decision-making and behaviour (Hemmonsbey and Tichaawa, 2021; Tessler et al , 2020). In addition, a correlation has been observed between wine exports and uptake in wine tourists interested in visiting wine-producing countries (Guedes et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the AFCON tournament being the main reason for the event attendees' travelling to Cameroon, it can be said that the event is a pull factor for primary travel and tourism. This is also empirically demonstrated in the most recent event leveraging studies of Hemmonsbey and Tichaawa (2021) who identified the traveling motives of event attendees in the context of major events. The AFCON is also a secondary reinforcement for (sport) tourism-related benefits as attendees with primary motives such as general tourism, visiting friends and family, as well as motives of business tourism, were attracted to the AFCON event and resulted in them purchasing tickets to various matches.…”
Section: Discussionmentioning
confidence: 65%